The History of a Hospital and Challenge of Expansion: CostEffectiveness and Surgical Coverage - Hama Amin Hussein, Abdulrahman; kadir Mahmood, Sanoor; Qadir Mahmood, Salah; Abdulkarim Nidhamaddin, Sakar (Kurdistan Journal of Applied Research, 2019)
The aims of this study are to estimate the cost-effectiveness of ophthalmic procedures that were performed after expansion at Shahid Aso Eye Hospital, to analyze how much cost the expansion and rebuilding this hospital can save to the local community and to estimate the expansion of ophthalmic surgical coverage after rebuilding of Shahid Aso Eye hospital. Data collected was based on the retrospective data documented in Shahid Aso Eye Hospital before its expansion, and after its rebuilding to a new specialized hospital from a small department, in addition to that the survey of new ophthalmic branches in different districts of Sulaimani Governorate was incorporated into this study. The number of operations performed, a number of doctors trained and an increase in surgical coverage were calculated. The results showed that there is an increase in the cost per quality-adjusted life year (QALY) gained with ophthalmic surgeries and DALY. Furthermore, there is an increase in the surgical coverage in all the districts of Sulaimani governorate. In addition, there is an additional benefit of reviving estimated lost money of about 2000, 000-4000, 000 USA dollars to the local market. In conclusion, expansion of Shahid Aso Hospital was beneficial for community from both health point of view and economically for the local market.